Long-term effect of treatment for non-muscle invasive bladder cancer on Quality of life: a cross-sectional study - Rikke Vilsbøll Milling; Ninna Kjær Nielsen; Charlotte Graugaard-Jensen; Peter Christensen; Helle Pappot; Jørgen Bjerggaard Jensen (Scandinavian Journal of Urology)
Background and objective: Approximately 75% of bladder cancer patients are diagnosed with non-muscle invasive bladder cancer (NMIBC). Complications from treatment, burden the patients and may affect their Quality of Life (QoL). Although accounting for most bladder cancer patients, only 25% of QoL research is conducted in NMIBC patients. The aim is to describe the incidence of complications and to investigate their long-term impact on QoL.